Seicento religioso: Nuovi dati sul "laboratorio" milanese = Seventeenth-Century and religious life : New data on Milanese “laboratory” - Zardin, Danilo (Rivista di storia della Chiesa in Italia, 2018)
This article focuses on some Seventeenth-Century Milanese illustrated texts which are generally neglected. It documents the liveliness of the religious town tradition after the changes imposed by the reforms of St. Charles Borromeo, showing its deep social roots and its capability to nourish in manifold forms the identity of the social community. The main sources of this essay are the edifying book by the Capuchin Ignazio Carnago, Città di rifugio a’ mortali, che contiene le divotioni dell’altissima signora madre di Dio e vergine immaculata (1655); the pamphlet celebrating the foundation of the «Accademia degli Spensierati», edited by the layman Baldassarre Migliavacca (La cena, 1633), and the devoted biography of a canon, who died in the odor of sanctity in 1666 (Santa vita e morte del venerabile sacerdote Luigi Cantova, 1717), written by his Jesuit nephew Giovanni Antonio Cantova.